2018
DOI: 10.4103/jips.jips_310_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study to evaluate bone loss during osteotomy using standard drill, bone trephine, and alveolar expanders for implant placement

Abstract: CBCT images showed minimum bone loss with the use of alveolar expander which may be due to the lateral bone condensation rather the removal of the marrow. Trephine showed less marrow removal in comparison to the standard drill used for dental implant surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The mean heat generated was maximum with the trephine (28.26±0.246 0C) followed by the conventional drill (27.27±0.297 0C) and least with alveolar expander (25.64±0.142 0C). The heat generated with the alveolar expander was minimum and it may be because there was lateral condensation of bone rather than removal of the marrow, which generates less heat ( 10 ). The researchers have indicated that an alveolar expander is an advantageous modality for implant osteotomy since the procedure is less invasive and easy to attempt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean heat generated was maximum with the trephine (28.26±0.246 0C) followed by the conventional drill (27.27±0.297 0C) and least with alveolar expander (25.64±0.142 0C). The heat generated with the alveolar expander was minimum and it may be because there was lateral condensation of bone rather than removal of the marrow, which generates less heat ( 10 ). The researchers have indicated that an alveolar expander is an advantageous modality for implant osteotomy since the procedure is less invasive and easy to attempt.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Bhargava et al( 10 ) where they evaluate the bone loss during osteotomy using the standard drill, bone trephine, and alveolar expanders for implant placement using cone-beam computed tomography. They found that osteotomy with an alveolar expander shows the minimum bone loss as seen on cone-beam computed tomography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation